Perilaku Petani dalam Menghadapi Risiko Usahatani Jagung di Kabupaten Lampung Selatan - Marlinda Apriyani; Bina Unteawati1 (Jurnal Ilmiah ESAI, 2010)
Rrisk in farm production is caused by the dependency of farming activity to the nature, in other words the bad influence of the nature has affected the total farming  production greatly. The farmer behavior in facing the risk and uncertainty will affect the food farm production efficiency. the courage of the farmers  to take risk is very influenced to the continuity of their corn farming business. The research showed that most of the farmer samples in south lampung region are neutral in facing the risk. meanwhile, the use of production factors in south lampung region has not been technically efficient, since the average of efficiency rate is below 100 percent. Key words : Corn Farming Risk,  Farmer Behavior, Use Of Production Factors